Comparação entre superfícies texturizadas para anel-cilindro através de simulação determinística - Silva, Samuel Anísio Nunes (2022)
A comparison of different textured surfaces is made using a deterministic simulation analysis of mixed lubrication with the main objective of indicating a surface that most benefits an application in a piston-cylinder pair of an internal combustion engine. The lubrication simulation solves the modified Reynolds equation proposed by Elrod-Adams for the calculation of the scaled hydrodynamic pressure and the scaled hydrodynamic shear-stress. In addition, the simulation calculates a Li and Chen approach of contact roughness model for Twin Land Oil Control Rings (TLOCRs) to obtain the asperity contact curves. Four original textured surfaces were characterized and they generated five additional surfaces, four of them after removing the peaked asperities (especially those around textures) and one had its texture density modified. The surfaces were simulated for twelve different speeds to cover the entire piston stroke. The results concluded that there is an indication for an application of the honed-textured surface with additional polishing in the regions of Top Dead Centre and Bottom Dead Cent, to avoid wear, and the application of a textured surface in the central region, in order to reduce fuel consumption. Additionally, removing protuberances around the texture pockets and decreasing texture density tends to increase hydrodynamic pressure.